PENGARUH PENERAPAN SISTEM AKUNTANSI KEUANGAN DAERAH DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Empiris Pada Pemerintah Daerah Kabupaten Tanah Datar) - Indri Apri Mayanti; Juita Sukraini; Siska Yulia Defitri (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to determine the effect of the implementation of the regional financial accounting system (X1) on the quality of regional government financial statements (Y), the influence of human resource competence (X2) on the quality of regional government financial statements (Y), and the simultaneous effect of the implementation of the financial accounting system. Regions (X1) and Human Resources Competence (X2) on the Quality of Local Government Financial Reports (Y). The results of the study show that there is an effect of the implementation of the Regional Financial Accounting System (X1) on the Quality of Local Government Financial Reports (Y). The results of testing the first hypothesis are proven by the value of|t_count | of 3.253 > 1.682 and the significance of t is 0.002 < 0.05. After that, there is an influence on Human Resource Competence (X2) Quality of Local Government Financial Reports (Y). The results of testing the second hypothesis are proven by the value of|t_count | of 9.888 > 1.682 and the significance of t is 0.000 <0.05. In addition, there is a simultaneous effect of the application of the Regional Financial Accounting System (X1) and Human Resource Competence (X2) on the Quality of Local Government Financial Reports (Y). The results of this third test are proven by the value of|F_hitung | of 136,404 > 3.23 and the significance of F is 0.000 < 0.05.